Statistical aspects of water quality monitoring : proceedings of the workshop held at the Canada Centre for Inland Waters, October 7-10, 1985 - El-Shaarawi, A. H.; Kwiatkowski, R. E., 1949- (Developments in water science ;, 1986)
This volume contains selected papers from the ``Workshop on the Statistical Aspects of Water Quality Monitoring'', held on October 7-10 1985, at the National Water Research Institute in Burlington, Ontario, Canada. The prime objective of the Workshop was to generate interaction between the statistical community and scientists working in the area of Water Quality Monitoring. To this end, topics covered in this Workshop fall into two categories: (1) Methods Development, and (2) the Imaginative Application of Existing Methodologies. Subjects covered include: Time Series, Estimation of Loading, Clustering, Model Development, Censoring Data Analysis, Quality Control and Data Acquisition. In the area of environmental sciences, statistical applications are still in their infancy, with few attempts to systematically develop techniques dealing with environmental issues. The publication of this book is one step towards identifying appropriate statistical techniques and diagnosing problems in Water Quality Monitoring which require new statistical methodologies. The papers presented in this volume represent international expertise, consolidating detailed information on both conventional and new methods.